2016
DOI: 10.5812/jhealthscope.39703
|View full text |Cite
|
Sign up to set email alerts
|

Contamination and Ecological Risk Assessment of Heavy Metals in Surface Soils of Esfarayen City, Iran

Abstract: Background: The urban soil characteristic is very important since numerous people live in cities nowadays. In recent decades, heavy metals enter into the urban environment due to the urbanization and different activities in cities. These metal contaminations can pose serious threats on community health. Contamination factor is a suitable tool for ecological geochemistry assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In this case, 73.91% of the sampled sites were considered moderate ecological risks attributed to the toxicity of metals released by anthropogenic activities such as industrial processes, agricultural practices, and natural sources (Mendoza et al, 2020). Our results are consistent with Suresh et al, 2012;Mohseni-Bandpei et al, 2017;Rehmana et al, 2018;da Silva et al, 2016;Mendoza et al, 2020). It had reported that Cd contributes significantly to the potential ecological risk index of the environment (Luo et al, 2012).…”
Section: Evaluating the Potential Ecological Risk Index (Ri) Of The H...supporting
confidence: 92%
“…In this case, 73.91% of the sampled sites were considered moderate ecological risks attributed to the toxicity of metals released by anthropogenic activities such as industrial processes, agricultural practices, and natural sources (Mendoza et al, 2020). Our results are consistent with Suresh et al, 2012;Mohseni-Bandpei et al, 2017;Rehmana et al, 2018;da Silva et al, 2016;Mendoza et al, 2020). It had reported that Cd contributes significantly to the potential ecological risk index of the environment (Luo et al, 2012).…”
Section: Evaluating the Potential Ecological Risk Index (Ri) Of The H...supporting
confidence: 92%
“…For the HMs content, As, Cd, Cr, and Ni were found to be varied from 4.05 to 29.89 mg/kg, 1.19 to 3.7 mg/kg, 257.25 to 3263.87 mg/kg, and 38.89 to 906.70 mg/ kg, respectively, with Cr, had the highest levels of concentrations followed by Ni, As and Cd. The total content of As, Cr, TOC, and Ni in the studied area had a great degree of variability, indicated by a substantial coefficient of variation (CV) values of 55.52%, Intervention Values, 2000), which has been widely used in heavy metals studies (Rudzi et al, 2018;Mohseni-Bandpei et al, 2017;Wu et al, 2018) and the 95% 'Investigation Levels' determined for Malaysia soil (Zarcinas et al, 2004), were also presented in Table 3. The levels of Cd, Cr, and Ni in the surface soil of the mining region were found to be greater than those values.…”
Section: Results and Discussion The Exploratory Analysis Of Soil Vari...mentioning
confidence: 99%
“…The contamination of groundwater is one of the most important environmental issues in the world [4] , [5] , [6] , [7] , [8] , [9] . Among the various pollutants that affect water resources, pollutants containing heavy metals are particularly important due to their high toxicity, even at low concentrations [10] , [11] , [12] , [13] . The parameters in the experiments of this research are including pH, TDS, EC, temperature and heavy metals (As, Hg, Pb, and Cd), in both season of winter and summer.…”
Section: Datamentioning
confidence: 99%